The Effect of Screen Exposure on Lecturer Health with Workload Mediation at the Indonesian University of Science and Technology - Rizta, Sri Utami; Nurjanah, Tarbiyah; Syafriani, Mona (Journal of Engineering Science and Technology Management (JES-TM), 2025)
The increasing use of digital technology in higher education has intensified screen exposure among lecturers, potentially affecting workload and health outcomes. This study examines the effect of screen exposure on lecturers’ health, with workload as a mediating variable, at the Indonesian University of Science and Technology. A quantitative causal-associative design was employed using a census method involving 65 permanent lecturers. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The analysis included validity and reliability testing, coefficient of determination (R²), predictive relevance (Q²), and hypothesis testing. The results indicate that screen exposure has a positive and significant effect on workload and a direct significant effect on lecturers’ health. However, workload does not have a significant direct effect on health and does not mediate the relationship between screen exposure and health. These findings suggest that adverse health effects related to screen exposure occur primarily through direct physiological and visual mechanisms. The model demonstrates strong explanatory and predictive power. This study contributes to empirical evidence on digital workload and occupational health in Indonesian higher education and offers practical implications for ergonomic and screen time management policies